The Directionality of Practices in the Definition of “Solidary”, “Anthropophagic”, or “Foreign” Consumption Patterns in the Space - Giordane dos Santos Costa, Breno; Pinto, Marcelo de Rezende (Organizações & Sociedade, 2024)
In the present paper, we demonstrate that the work developed by the Brazilian geographer Milton Santos is suitable for studies in the field of practices and consumption. When we use the term ‘practice’ we are referring to a specific kind of practice that is found in the strand of theory created by Schatzki’s work. More specifically, with this merge, we created the construct of directionality of practices. Looking at this dimension, the researchers can see the origin of practices and the consequent consumption patterns in the places. As we argue, “solidary” consumption is created by horizontal practices, “foreign” consumption is created by vertical practices, and “anthropophagic” consumption is created by undifferentiated practices. We expect that this paper can also contribute to giving room for Milton Santo’s work in the field of consumption studies.